Outside looking in : a novel - Boyle, T. Coraghessan (Ecco, an imprint of HarperCollinsPublishers, 2019)
A novel inspired by the controversial psychedelic drug experiments of Timothy Leary traces the impact of LSD and communal living on a 1960s Harvard grad student and his wife.